2007
DOI: 10.1111/j.1600-0420.2006.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the epithelium in organ‐cultured donor corneas with extended post‐mortem time

Abstract: ABSTRACT.Purpose: The maximum post-mortem time limit for obtaining donor corneas varies between eye banks. It is not known for how long a time the epithelial cells survive post-mortem, nor is it known if donor corneas with extended postmortem time are able to regenerate the epithelium. Therefore, we wanted to examine the epithelium in donor corneas for regenerative ability during storage in an eye bank organ culture system. Methods: Twenty-four paired donor corneas with post-mortem time from 28 to 163 hr were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…An absent or partially absent epithelium increases the potential for trauma from exposure, medications used in preparation of the donor or preservation medium. Disintegration of certain structural proteins or adhesion molecules contribute to the loosening of cells, especially if the basal cells are weakly attached to the central cornea (Van Meter et al 2005;Slettedal et al 2007). Such changes may lead to the apoptosis of anterior stromal keratocytes, and it has been shown that these effects might be prolonged (Wilson et al 2001;Erie 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An absent or partially absent epithelium increases the potential for trauma from exposure, medications used in preparation of the donor or preservation medium. Disintegration of certain structural proteins or adhesion molecules contribute to the loosening of cells, especially if the basal cells are weakly attached to the central cornea (Van Meter et al 2005;Slettedal et al 2007). Such changes may lead to the apoptosis of anterior stromal keratocytes, and it has been shown that these effects might be prolonged (Wilson et al 2001;Erie 2003).…”
Section: Discussionmentioning
confidence: 99%
“…No general agreement exists on the maximum time limit for removing donor corneas, and this time limit varies greatly between eye banks. It is recommended that corneal preservation occurs as soon as possible after death (Slettedal et al 2007), but some researchers claim that there are no such upper time limits: as long as certain quality criteria are met, corneas can be used for grafting (Andersen & Ehlers 1988;Ehlers 2002). Another controversy exists regarding donor age as the factor that may determine the suitability of a cornea for transplantation (Gal et al 2008).…”
mentioning
confidence: 99%
“…For organ culture, donor corneas were incubated as described previously (Slettedal et al 2007). For organ culture, donor corneas were incubated as described previously (Slettedal et al 2007).…”
Section: Tissuementioning
confidence: 99%
“…The corneal storage protocol was effective to provide tissues with intact epithelium, 34,35 and no damage to the epithelial cells was found after transepithelial corneal crosslinking. In order to avoid any bias due to changes in the hydration state during the experiment, the corneal tissues were kept in 20% dextran solution overnight before AFM testing.…”
Section: 27-29mentioning
confidence: 99%